2013
DOI: 10.1007/s40595-013-0001-6
|View full text |Cite
|
Sign up to set email alerts
|

Big data as the new enabler in business and other intelligence

Abstract: The term "big data" will always be remembered as the big buzzword of 2013. According to the Wikipedia, big data "is a collection of data sets so large and complex that it becomes difficult to process using on-hand database management tools". In other perceptions, the "3 Vs" that characterize it (i.e., volume, velocity, and variety) or the "4 Vs" (adding veracity to the previous three) are responsible for the fact that it exceeds an organization's own data as well as its storage or compute capacity for accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 18 publications
0
21
0
6
Order By: Relevance
“…Embedding BDA in BPMS may give "process participants better real-time situational awareness and the ability to tailor their responses appropriately" (Gao, 2013, p.4). According to Vossen (2013) and Vera-Baquero et al (2015), BDA capable BPMS need to be analytical, automatic, adaptive, and agile to leverage big data (Hill and Schulte, 2011;Gao, 2013) and this makes the system capable of advanced analysis while automatically processing data from several different business processes (Wamba and Mishra, 2017). Additionally, when applied to two or more related organizations, these systems may foster inter-organizational information exchange (Vera-Baquero et al, 2015).…”
Section: Big Data Business Process Management Systems and Ambidextrmentioning
confidence: 99%
“…Embedding BDA in BPMS may give "process participants better real-time situational awareness and the ability to tailor their responses appropriately" (Gao, 2013, p.4). According to Vossen (2013) and Vera-Baquero et al (2015), BDA capable BPMS need to be analytical, automatic, adaptive, and agile to leverage big data (Hill and Schulte, 2011;Gao, 2013) and this makes the system capable of advanced analysis while automatically processing data from several different business processes (Wamba and Mishra, 2017). Additionally, when applied to two or more related organizations, these systems may foster inter-organizational information exchange (Vera-Baquero et al, 2015).…”
Section: Big Data Business Process Management Systems and Ambidextrmentioning
confidence: 99%
“…On the basis of the information received, the actuators make the necessary decisions about how to respond to the appropriate actions. It creates, however, a new type of data, big data, James [9], Vossen G [19] -a large number of datasets in the streaming and dynamic forms. Thus, we need a new approach that seeks to discover new information, identify and categorize data, focusing on exploring natural phenomena, acquiring new knowledge, and understanding real-time laws of nature.…”
Section: The Real World and Virtual Worldmentioning
confidence: 99%
“…They concluded that big data analytics can be applied to leverage business changes and enhance decision-making by applying advanced analytics techniques on big data and revealing hidden insights and valuable knowledge. Vossen (2014) studied and reviewed the issues, techniques and applications of big data, with an emphasis on business intelligence architectures. Saecker and Markl (2013) then presented an overview of existing processing approaches to address the problems arising from big data analytics when using modern hardware architectures.…”
Section: Big Data and Big Data Analyticsmentioning
confidence: 99%